Analisis Ketersediaan dan Kebutuhan Sarana dan Prasarana Permukiman Nelayan di Negeri Ureng Kecamatan Leihitu (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
Indonesia is an archipelagic country consisting of 17,504 islands (Law No. 6 of 1996 concerning Indonesian Waters), has a variety of unique and natural potentials spread from Sabang to Merauke. Negeri Ureng is located on the north coast of Leihitu District, Central Maluku Regency. It consists of 4 (four) regions, including the Seram Sea and West Seram Regency to the north, Ambon City to the south, Negeri Lima Village to the west, and Assilulu Village to the east. The area covers 468.75 ha with a population of 6,704 people. There are 460 residents who make a living as fishermen, with a percentage of 15.93% of the total population according to occupation of 2,866 people. The purpose of this study was to determine the level of availability and need for fishing facilities and infrastructure in Negeri Ureng. The method used in this study is descriptive qualitative and scoring analysis. From the analysis results, it is known that the level of availability of basic facilities and infrastructure in the Negeri Ureng fishing settlement has a total value of 21.53 and the level of need, among others, requires one TPI unit, boat mooring, fish drying area, pier, market repair, dredging of canals and addition of canal stairs, and 5659 meters of drainage are needed to meet service standards.